Pelatihan Pemetaan Lahan Pertanian dengan Penginderaan Jauh di Dinas Pertanian Kota Kupang - Frederika Rambu Ngana; Jehunias Leonidas Tanesib; Ali Warsito; Laura Anastasi Seseragi Lapono; Zakarias Seba Ngara; Redi Kristian Pingak (Abdi Geomedisains, 2025)
The Physics Study Program, Faculty of Science and Engineering, Nusa Cendana University, conducted a Community Service (PkM) activity at the Department of Agriculture in Kupang City on September 24, 2024. The partners in this community service activity were the Department of Agriculture in Kupang City, Nusa Tenggara Timur Province. The partners faced a challenge in manually measuring the area of agricultural land, particularly in remote areas. Therefore, the PkM team provided training in agricultural land mapping using remote sensing to its partners. This training aims to enhance the capacity of its partners in mapping agricultural land using remote sensing and calculating the area of agricultural land based on the agricultural land map. The implementation method involves conveying basic concepts of remote sensing, map data collection, and direct practice in creating agricultural land maps. In this activity, the administrative map of Kupang City was taken from the Indonesian geospatial website. Then, participants collected agricultural land cover data using a GPS device. The remote sensing data used was Landsat 9 imagery from the USGS website. The Landsat 9 imagery was classified according to the type of agricultural land. The software was QGIS, SAGA, and Google Earth. The training results demonstrated an increase in the partners' knowledge and skills in making agricultural land maps using remote sensing. Partners were also able to calculate agricultural land area based on the agricultural land map. This training provided positive feedback, as partners will use the agricultural land map as a reference for regional planning in Kupang City.